1999
DOI: 10.1021/ja9835234
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Effects of Methyl and Methyl Ester Groups on the Nucleation and Growth of Vapor-Deposited Aluminum Films

Abstract: The interaction of vapor-deposited Al atoms with self-assembled monolayers (SAMs) of HS(CH2)15CH3 and HS(CH2)15CO2CH3 chemisorbed at Au{111} surfaces was studied using X-ray photoelectron spectroscopy, infrared spectroscopy, time-of-flight secondary ion mass spectrometry, and spectroscopic ellipsometry. For the CH3-terminated SAM, no reaction with C−H or C−C bonds was observed. For total Al doses up to ∼12 atoms/nm2, penetration to the Au−S interface occurs with no disruption of the average chain conformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
319
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(353 citation statements)
references
References 55 publications
(86 reference statements)
32
319
2
Order By: Relevance
“…Recent studies have focused on the interaction between the ester functional group and sputter-deposited metal atoms, such as aluminium and chromium. 27,28 Both of these studies provided evidence for the formation of complexes between metal atoms and the ester functional group. In both cases, it has been suggested that the ester molecule remains intact with the attachment of metal atoms to the carbonyl group.…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies have focused on the interaction between the ester functional group and sputter-deposited metal atoms, such as aluminium and chromium. 27,28 Both of these studies provided evidence for the formation of complexes between metal atoms and the ester functional group. In both cases, it has been suggested that the ester molecule remains intact with the attachment of metal atoms to the carbonyl group.…”
Section: Discussionmentioning
confidence: 94%
“…In the case of penetration of nascent metal atoms through dynamic, transient defects, insertion into SÀAu bonds can occur, and if the new S-metal-Au bonding is stronger than S-Au bonds this can result in diminishing of the lateral fluctuations, thereby stopping formation of the temporal vacancy channels, thus limiting the extent of penetration. On the other hand, this freezing process of the lateral positional fluctuation may also lead to new static defects because of the continuing disordering of the SAM molecule positions driven by the incommensurate non-uniform insertion of deposited metal into the SAM-substrate interface [20,21]. In order to avoid introducing chemical reaction products into the junction via reactions of the deposited metal with the SAM and to avoid oxidation or corrosion of the top contact, inert or low reactive metal species, such as Au, Ag, Cu, and Pd, have been used [22][23][24][25][26][27][28].…”
Section: Overview and General Considerationsmentioning
confidence: 99%
“…Since Al is an important metal for device applications its deposition on SAMs has been extensively studied [20,21,23,32,33,41,50,[65][66][67][68][69]. The critical problem for Al, however, is its facility in penetration along with filament growth.…”
Section: Almentioning
confidence: 99%
“…At present, the mechanism of ester decomposition on aluminum is unknown. 41,42 Recent spectroscopic work by Hooper et al 43 on an idealized system revealed that vapor-deposited aluminum atoms will react with the CO 2 CH 3 group in a self-assembled monolayer (SAM) of HS CH 2 15 CO 2 CH 3 but will not react with the CH 3 groups in a SAM of HS CH 2 15 CH 3 . Underhill and Timsit 44 investigated the decomposition of short-chain alcohols and carboxylic acids on a clear aluminum surface across a range of temperatures.…”
Section: Review Of the Literaturementioning
confidence: 99%